If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=6=42
We move all terms to the left:
y-(6)=0
We move all terms containing y to the left, all other terms to the right
y=6
| k/9=10/88 | | 9.78=c+3.14 | | H(t)=-4t^2+6t-1 | | 2y=-68+3(5y+1) | | 5^x-1=5^3x-11 | | v+5.8=19.2 | | 5-4-3x=-36 | | p/2=1.54 | | 3x+(x-14)=33 | | 8u=456 | | 8u=455 | | n+(n+1)+(n+2)+(n+3)+55=3(n+4) | | c/27=7 | | -5y(y-5)=-3y+45 | | 8-2(12+12)=5-2x-13 | | 5-4|-3x|=-36 | | r-5=43 | | -4b=-8-6b^2+4b | | c+25=671 | | 4+9.75x=0.25x+ | | 5+5(n-1)=19 | | -(x+3)+4x=6 | | n+(n+1)+(n+2)+(n+3)+(n+4)=55 | | 10+7.5n=8+7.9n | | 128=k-39 | | h+94=891 | | (2x+7)=65 | | v+9-48=1 | | h+94=894 | | –17+15z=13z+19 | | 2n+8=60 | | 459=27g |